Blood calcium levels in factory workers who consume supplements drinks - Chalies Diah Pratiwi; Hariyanto Hariyanto; Amelia Rahma Perdana Putri (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2019)
Energy supplement drinks are drinks that contain caffeine, taurine, sweeteners, and other substances that have the effect of increasing energy, concentration, alertness, maintaining physical strength, and reducing drowsiness. Blood calcium is an important mineral that the body needs. The purpose of this study was to determine blood calcium levels in marble factory workers in Besole Village, Tulungagung Regency. The research design used was Analytical Descriptive. The population in this study were all marble factory workers who routinely consumed energy supplement drinks in the village of Besole in 2018 using a total sampling technique of 30 respondents. This research was conducted at the Laboratory of Dr. Iskak Tulungagung in May 2018 using the O-CPC method. The results obtained from the examination of blood calcium in marble factory workers showed 10 respondents (33%) had blood calcium levels within normal limits, 17 respondents (57%) had deep blood calcium levels. low limit and 3 respondents (10%) had very low blood calcium levels. Consumption of energy supplement drinks that exceed the threshold can damage the kidneys and affect blood calcium levels because the caffeine content in energy supplements can increase the release of calcium in the bones so that more calcium is released through the urine.